Photosynthetic Pigments Changes of Three Phenotypes of Picocyanobacteria Synechococcus sp. under Different Light and Temperature Conditions - Sylwia Śliwińska-Wilczewska; Zofia Konarzewska; Kinga Wiśniewska; Marta Konik (Cells, 2020)
It is estimated that the genus Synechococcus is responsible for about 17% of net primary production in the Global Ocean. Blooms of these organisms are observed in tropical, subtropical and even temperate zones, and they have been recorded recently even beyond the polar circle. The long-term scenarios forecast a growing expansion of Synechococcus sp. and its area of dominance. This is, among others, due to their high physiological plasticity in relation to changing environmental conditions. Three phenotypes of the genus Synechococcus sp. (Type 1, Type 2, and Type 3a) were tested in controlled laboratory conditions in order to identify their response to various irradiance (10, 55, 100 and 145 µmol photons m−2 s−1) and temperature (15, 22.5 and 30 °C) conditions. The highest total pigment content per cell was recorded at 10 μmol photons m−2 s−1 at all temperature variants with the clear dominance of phycobilins among all the pigments. In almost every variant the highest growth rate was recorded for the Type 1. The lowest growth rates were observed, in general, for the Type 3a. However, it was recognized to be less temperature sensitive in comparison to the other two types and rather light-driven with the highest plasticity and adaptation potential. The highest amounts of carotenoids were produced by Type 2 which also showed signs of the cell stress even around 55 μmol photons m−2 s−1 at 15 °C and 22.5 °C. This may imply that the Type 2 is the most susceptible to higher irradiances. Picocyanobacteria Synechococcus sp. require less light intensity to achieve the maximum rate of photosynthesis than larger algae. They also tolerate a wide range of temperatures which combined together make them gain a powerful competitive advantage. Our results will provide key information for the ecohydrodynamical model development. Thus, this work would be an important link in forecasting future changes in the occurrence of these organisms in the context of global warming.